2020
DOI: 10.1371/journal.pbio.3000930
|View full text |Cite
|
Sign up to set email alerts
|

TOP1α, UPF1, and TTG2 regulate seed size in a parental dosage–dependent manner

Abstract: Cues of maternal and paternal origins interact to control seed development, and the underlying molecular mechanisms are still far from clear. Here, we show that TOPOISOMERASE Iα (TOP1α), UP-FRAMESHIFT SUPPRESSOR 1 (UPF1), and TRANSPARENT TESTA GLABRA2 (TTG2) gametophytically, biparentally regulate seed size in Arabidopsis. TOP1α and UPF1 are mainly expressed in antipodal cells, and loss of their function leads to ectopic TTG2 expression in these female gametophytic cells. We further demonstrate that TOP1α and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Transparent testa glabra 2 ( TTG2 , also known variously as ATWRKY44, DR. STRANGELOVE 1, DSL1, F3G5.5, F3G5_5, or WRKY44 in the NCBI entry for the Arabidopsis thaliana gene NP _181263) is a transcription factor whose mutant phenotypes in A. thaliana include altered seed color [ 35 ], and reduced seed size [ 36 , 37 ]. A putative ortholog is differentially expressed in relation to seed development in Fagopyrum esculentum (common buckwheat) [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transparent testa glabra 2 ( TTG2 , also known variously as ATWRKY44, DR. STRANGELOVE 1, DSL1, F3G5.5, F3G5_5, or WRKY44 in the NCBI entry for the Arabidopsis thaliana gene NP _181263) is a transcription factor whose mutant phenotypes in A. thaliana include altered seed color [ 35 ], and reduced seed size [ 36 , 37 ]. A putative ortholog is differentially expressed in relation to seed development in Fagopyrum esculentum (common buckwheat) [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…TTG2 plays a key role in seed coat color, through the regulation of genes involved in the intracellular transport of proanthocyanidins (tannins) [ 35 , 46 ]. TTG2 is also involved in seed size, as noted for Arabidopsis mutations and in a network study of agronomic traits in barley [ 36 , 37 , 47 ]. Conceivably, selection for a gene knockout might have occurred in quinoa selected for lighter seed color, but that would not be consistent with the typical black seed color of our Canadian C. berlandieri accession.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis has consistently shown TOP1α and UPF1 function upstream of TTG2. TTG2 is directly suppressed by TOP1 and UPF1 by causing a chromatin disruption [ 25 ]. Further, it has been suggested that comparative TTG2 quantity in antipodal cells to gametes regulates seed size, indicating the role of the maternal and paternal dose-dependent molecular framework.…”
Section: Genetic Factors Controlling Seed Sizementioning
confidence: 99%
“…It has been suggested also, that PAs are involved in seed development resulting from interploidy crosses 6 . Mutation of maternally-expressed genes, such as TRANSPARENT TESTA GLABRA 2 ( TTG2 ) and TRANSPARENT TESTA 4 ( TT4 ), involved in PA biosynthesis, a branch of the flavonoid biosynthesis pathway (FBP), can partially suppress F1 seed lethality caused by paternal-excess interploidy crosses in Arabidopsis thaliana 6 , 22 , 41 . Although much progress has been made in identifying genetic modifiers of the triploid block, most of the advances to date have focused on the paternal elements responsible for (i) the high sensitivity of Arabidopsis thaliana to increased paternal genome dosage and, (ii) the triploid block 31 , 42 , 43 .…”
Section: Introductionmentioning
confidence: 99%